Edital mecenas do Ceará: uma avaliação das políticas de incentivo à cultura, a partir da vivência de profissionais da produção cultural - Camelo, Camila Maria Guerra (2023)
The general objective of this work is to evaluate the mechanism of access to the public resource managed by the Law of the State System of Culture (SIEC), called Edict Mecenas do Ceará, based on the experience reports of cultural production professionals who work in the state, who submitted , as proponents, cultural projects to the aforementioned public notice, having executed or that are executing projects with financial resources arising from this law. To achieve this objective, it is initially intended to analyze federal and state cultural incentive policies, based on the evaluative axes of in-depth evaluation, as proposed by Gussi (2014, 2017), Gussi and Oliveira (2016), considering, therefore, in this evaluation, the experience of the actors involved in the design, application, use and evaluation of cultural policy results. Then, it is intended to investigate who are the professionals of cultural production and how they perceive their relationship with public policies to encourage culture in the state of Ceará, specifically dealing with incentives via tax waiver. Finally, we seek to understand how these professionals see themselves as actors in the design of these state cultural policies, and to investigate their understanding of the spot of cultural production within the sector's productive chain, based on their professional experiences. For this work, a qualitative approach is used, with bibliographical research of renowned authors in the field of research on culture, public policies, and cultural policies, such as Albino Rubim, Lia Calabre and Alexandre Barbalho. In addition to research in the texts of laws, decrees and other documents and journalistic articles that make it possible to reconstruct the temporal and territorial trajectory of policies. As an approximation to the field, cultural production professionals were interviewed, with content analysis carried out based on Bardin's methodology (2016), to apprehend the perceptions of these active professionals about their roles in the field and in the productive chain of culture, about policies public incentives for culture in force in the state of Ceará.